Mahmoud Ayoub and Christian-Muslim relations - Yusuf, Imtiyaz (Oxford University Press, 2024)
Mahmoud Mustafa Ayoub was the foremost North American Muslim scholar of Muslim-Christian relations and interreligious dialogue in the modern age who offered new interpretations concerning the roots of conflict between Islam and Christianity. He also offered a new theological approach for building better Muslim-Christian understanding. Ayoub also made methodologically original contributions to the study of Shi’i Islam, tafsir al-Qur’an—Qur’anic exegesis, and building Taqrib al-Madhahib—Sunni-Shi’i ecumenism.